Persepsi Gen Z terhadap Pesan Kesehatan Mental di Media Sosial: Analisis Deskriptif atas Fenomena Self-diagnose di Kalangan Generasi Z - Nahari, Muhammad Javier Ramadhan; Sumardjijati, Sumardjijati (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study aims to understand how Generation Z perceives mental health messages on social media and how these perceptions relate to self-diagnosis tendencies. Employing a qualitative descriptive approach, the research involved seven active users of TikTok and X who had previously self-diagnosed after engaging with mental health-related content. Data were collected through in-depth interviews and content observation, then analyzed using the Miles, Huberman model. The findings reveal that mental health messages are interpreted emotionally and contextually, shaped more by personal experience than professional knowledge. The novelty of this study lies in integrating social perception theory to explain how Gen Z constructs meaning from digital messages while highlighting the mediating role of media literacy in self-diagnosis. The results contribute theoretically to digital health communication studies and offer a foundation for designing empathetic and evidence-based communication strategies on social media platforms.